2002
DOI: 10.1186/1471-2180-2-6
|View full text |Cite
|
Sign up to set email alerts
|

First isolation of the enterohaemorrhagic Escherichia coli O145:H- from cattle in feedlot in Argentina

Abstract: Background: Enterohaemorrhagic Escherichia coli (EHEC) is considered to be common cause of haemorrhagic colitis (HC), thrombotic thrombocytopenic purpura and haemolytic uraemic syndrome (HUS) in humans. In a previous paper, we have demonstrated that EHEC are commonly found in the intestines of livestock. Infections in humans are, in part, a consequence of consumption of undercooked meat or raw milk. Argentina has one of the highest records of HUS (300-400 cases/year; 22/100,000 children under 4 years of age). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 23 publications
1
5
0
1
Order By: Relevance
“…Following individual O157 strain isolation, those samples positive for the eae-c gene were subjected to immunomagnetic separation (IMS), a rapid method used for detecting O157 strains. The methods described by Padola et al (2004) were followed. Samples were inoculated in peptone water supplemented with antibiotics (0.05 mg cefixime l 21 , 8 mg vancomycin l 21 , 10 mg cefsulodin l 21 ) and incubated with shaking at 37 uC for 6 h. One millilitre of each sample was then subjected to IMS with polystyrene magnetic beads coated with antibody specific for O157 (Dynal) as described by Lindqvist et al (1998).…”
Section: Bacteriological Procedures and Analysis Of Virulence Genesmentioning
confidence: 99%
“…Following individual O157 strain isolation, those samples positive for the eae-c gene were subjected to immunomagnetic separation (IMS), a rapid method used for detecting O157 strains. The methods described by Padola et al (2004) were followed. Samples were inoculated in peptone water supplemented with antibiotics (0.05 mg cefixime l 21 , 8 mg vancomycin l 21 , 10 mg cefsulodin l 21 ) and incubated with shaking at 37 uC for 6 h. One millilitre of each sample was then subjected to IMS with polystyrene magnetic beads coated with antibody specific for O157 (Dynal) as described by Lindqvist et al (1998).…”
Section: Bacteriological Procedures and Analysis Of Virulence Genesmentioning
confidence: 99%
“…In Colombia, E. coli O157 was isolated in 6.5 % of 307 rectal swabs from cattle (Mattar & Vásquez, 1998). The prevalence of E. coli O157 in healthy young beef steers and grazing-fed cattle in Argentina was 0.5 and 6.8 %, respectively (Meichtri et al, 2004;Padola et al, 2004), whilst similar studies in Brazil have shown rates of 0.6 % in dairy cattle (Irino et al, 2005), and 1.5 % in beef and dairy calves (Cerqueira et al, 1999). In developed countries, the prevalence rates of E. coli O157 : H7 vary considerably from 1.8 % in Japan (Miyao et al, 1998) to 23 % in the USA (Smith et al, 2001).…”
Section: Serum Bactericidal Activitymentioning
confidence: 99%
“…A total of 95 strains were selected from a well characterized, previously described strain collection of our Laboratory. To assess potential associations among subA, other virulence factors and serotypes, we selected representative strains taking into account the presence of vt 1 , vt 2 , eae, saa, and ehxA genes determined in previous studies (15,16,22). In the present work, a previously described multiplex PCR, which detects subA, vt 1 and vt 2 , was used for subA screening (20).…”
mentioning
confidence: 99%